MORPHOFUNCTION ASPECTS OF THE DIGESTIVE ORGANS OF THE ANTERIOR COMPARTMENT OF CHICKENS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
This article provides information on the scientific work of scientists on the postnatal morphogenesis of the digestive organs of chickens. The analysis of the literature shows that the morphofunctional features of the structure of the glandular and muscular stomach from the organs of the front part of the digestive system of birds, as well as their formation and development, are influenced by factors. Knowing the morphological characteristics of the structure of the digestive tract of chickens creates a basis for rational and effective use of feed, prevention and treatment of gastrointestinal diseases in poultry. In this regard, it is of great importance to study the macro- and micromorphological features of the structural components of the foregut of birds.